Adolescent adjustment to parental divorce : an investigation from the theoretical perspective of structural family therapy - Abelsohn, David Selwyn (Department of Psychology, 2026)
Significant Aided-Unaided differences are also found: Aided families are perceived as more chaotic, disengaged, and enmeshed than Unaided families; Aided adolescents are characterized by more Externalizing (i.e . acting out) behavior problems than Unaided adolescents; and while all Unaided adolescents fall within the nonclinical normative range on the standardized test on Externalizing Problems, more than one third of Aided adolescents fall within the clinical range on this test. Further, significant differences in mothers' postseparation incomes are found between the Aided and Unaided groups, with the Aided being lower. Comparisons of the adjustment scores for the combined Aided plus Unaided groups with the test norms of the clinical and nonclinical standardization groups reveal that the adolescents as a group fall between the clinical and nonclinical norms, suggesting that divorce is a stressor for these adolescents which is within the realm of nonclinical, or nonsymptomatic, adaptation. These findings represent a first quantitative attempt with separated families to (a) demonstrate that individual adolescent adjustment is contingent on structural features of the family, and (b) differentiate in one study between characteristics of Aided and Unaided families and their adolescents. This is an important methodological issue which has not been controlled in previous studies. (iii) (2) Two qualitative clinical case studies demonstrate the pertinence of these family dimensions, both in understanding the plight of clinical postseparation families with adolescents and in guiding their treatment. The first family is characterized by disengagement and a collapsed Generational Hierarchy. The second family is characterized by rigid enmeshment and disengagement in the mother-son and father-son subsystems respectively. Finally , the family dimensions are employed to understand the successful efforts of a nonclinical , separated family with an adolescent to adapt over a 3- year period after the separation . As far as is known, these case studies are the first systematic attempt to apply these structural family concepts to postseparation families. Thus , the contribution of this thesis to our current understanding of the adjustment of adolescents to their parents' separation represents a first attempt to (a) quantitatively relate adolescent adjustment to structural dimensions of the family , and to differentiate between characteristics of Aided and Unaided families and their adolescents, and (b) qualitatively demonstrate the applicability of these structural dimensions in the clinical situation, and to understand the successful efforts of a nonclinical family to adapt after a separation.